2019
DOI: 10.1039/c8mh01527a
|View full text |Cite|
|
Sign up to set email alerts
|

Non-spherical micro- and nanoparticles in nanomedicine

Abstract: This review provides insights into the role of particle geometry in biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 263 publications
1
92
0
Order By: Relevance
“…The flower shape refers to the geometrical resemblances to a flower, with pyramid-like petal dimensions of less than 100 nm [ 30 ]. Flower-like nanostructures can disrupt the cell wall and cell mechanisms better than spherical shapes, thus promoting the death of human endothelial cells [ 31 , 32 ]. Therefore, the flower shape indicates that this substance can be a potential candidate for cancer drug delivery.…”
Section: Resultsmentioning
confidence: 99%
“…The flower shape refers to the geometrical resemblances to a flower, with pyramid-like petal dimensions of less than 100 nm [ 30 ]. Flower-like nanostructures can disrupt the cell wall and cell mechanisms better than spherical shapes, thus promoting the death of human endothelial cells [ 31 , 32 ]. Therefore, the flower shape indicates that this substance can be a potential candidate for cancer drug delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Particle shape and morphology are important parameters in luences various biological and processes, including biodistribution, cellular uptake, and subsequent traf icking within cells (Zhu et al, 2019). It has been reported that the toxicity of the nanoparticle depends on the shape of the nanoparticles.…”
Section: Shape and Morphologymentioning
confidence: 99%
“…The size and shape of particles can affect their biological behavior in vivo [ 22 , 23 ]. Decuzzi et al demonstrated that discoidal particles accumulate in significantly higher concentrations in the lungs than spherical particles or quasi-hemispherical particles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%